2016
DOI: 10.1016/j.ijheatmasstransfer.2016.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Figure-of-merit for phase-change materials used in thermal management

Abstract: a b s t r a c tIn this work, we utilize a figure-of-merit (FOM) to compare the performance of various phase-change materials (PCMs) in managing short bursts of high-power heat flux, particularly those associated with microprocessors undergoing bursty operation on a time scale of approximately one second. We numerically investigate the FOM for applications that have realistic boundary conditions and lack analytical solutions. We also fabricate microprocessor proxies with integrated PCM compartments mounted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…[1][2][3] Phase change materials (PCMs) are energy storage materials which can absorb or release a huge amount of heat during the phase change process. 4,5 Because of their merits, which consist of high energy storage density and environmentfriendly features, PCMs have aroused much attention for their applications in many elds such as the construction industry and transportation. 6,7 PCMs can be divided into three categories according to the chemical composition of the inorganic, organic and eutectic phase change materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Phase change materials (PCMs) are energy storage materials which can absorb or release a huge amount of heat during the phase change process. 4,5 Because of their merits, which consist of high energy storage density and environmentfriendly features, PCMs have aroused much attention for their applications in many elds such as the construction industry and transportation. 6,7 PCMs can be divided into three categories according to the chemical composition of the inorganic, organic and eutectic phase change materials.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, intermediate rhombohedral (R-phase) and orthorhombic B19 phases will form during this process. 7 In addition to the Martensitic phase transformation, NiTi alloys have a number of attractive properties, including excellent corrosion resistance 8 , high strength and ductility 9 , and good formability via traditional thermomechanical processing, machining, and additive manufacturing. 10 Two 1 mm thick commercial NiTi alloy plates with different transformation temperatures were purchased to demonstrate the ability of SMAs to function as SS-PCMs.…”
mentioning
confidence: 99%
“…Togive an accurate representation of the available data, the FOM values inTable S1have been presented as a range calculated with the high and low reported Austenite values of 15.6-28 W/m·K. This is appropriate because the FOM is generally calculated based on the thermal conductivity of the high temperature phase, in this case the Austenite phase 7. The green band on the abstract imagereflects these calculated high and low literature values for the range of NiTi materials.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] They also have been found to be effective for thermal applications on a shorter time scale such as high flux thermal transient mitigations. [9][10][11][12] This is a result of lower degrees of subcooling, higher thermal conductivities and high volumetric storage capacities exhibited by metallic PCMs. 13,14 Shobo et al 14 also reported that a metallic PCM (In-48Sn) showed very good thermal cycling stability, over repeated charging/discharging cycles, compared to its organic counterparts.…”
Section: Introductionmentioning
confidence: 99%